The Use of Social Media for Collaborative Learning Towards Improved Students' Performance in University of Ilorin - Ojo, 0. J (International Journal of Educational Management, 2025)
Social media in its entirety has affected humans in various fields of life endeavours and the rate is still on the increase. Is usage in higher institutions of learning across the globe has affected students' academic performance and this has aggrandized concern among stakeholders. On this basis, the study leaned towards the investigation of the perception of undergraduates on social media usage as a way of facilitating learning towards improved student's performance in University of Ilorin, Nigeria. The study adopted descriptive design of explorative type. The study population are undergraduate students of the 15 faculties in University of Ilorin. The faculties were stratified into two i.e Humanities and sciences. Thereafter, the respondents were selected randomly from five faculties in the University. A well validated researcher-design questionnaire was used for data collection and it was titled "stakeholder's perception of social media usage for collaborative learning towards improved student's performance" (SPSMCLSP). The research questions raised were analyzed with the aid frequency and percentages. Major findings revealed that interactive platforms social media- to be effectively used among students towards collaborative learning for improved academic performance. The study recommended that school administrators should enhance the usage of media platforms for learning because it helps acquire information much faster and easier compare lo classroom. Also, students should posses' basic understanding of media platforms and its usage to enhance collaborative learning for better performance.